Explicating the salinity tolerance of cowpea (Vigna unguiculata L. Walp.) genotypes at seed germinating stage: Salinity tolerance of cowpea (Bangladesh Journal of Agriculture, 2024)
Cowpea is an important food and fodder legume in the arid and semi-arid tropics of the world. Soil salinity adversely affects seed germination, which ultimately reduces crop production. The present study was carried out to screen the cowpea germplasm and identify the salinity tolerant genotypes at the germination stage. Initially, an experiment with five salinity levels (0, 50, 100, 200, and 250 mM of NaCl) was conducted, and the results showed that 200 mM of NaCl concentration could be a sensible salinity stress to assess the salinity tolerance of cowpea genotypes. A total of 29 cowpea genotypes were evaluated under a 200 mM NaCl concentration. Four salinity tolerance indices  such as  absolute decrease (AD), inhibition index (II), relative salt tolerance (RST), and salt tolerance index (STI) were calculated from germination percentage without stress (GC) and germination with 200 mM  NaCl (GS). All the indices showed significant variation in responses to salinity stress among the cowpea genotypes. The results revealed that salinity stress significantly reduced the germinating percentage in cowpea. Total seven cowpea genotypes (G4, G9, G12, G15, G26, G27, and G32) were found to be salinity tolerant lines at the germination stage. The seven genotypes were clustered  in the same group which had the higher RST (G4: 0.58, G9: 0.80, G12: 0.50, G15: 0.60, G26: 0.50, G27: 0.60, and G32: 0.80) and STI (G4: 0.58, G9: 0.80, G12: 0.50, G15: 0.60, G26: 0.50, G27: 0.60, and G32: 0.79) under salinity stress. However, this is a preliminary screening against salinity at the germination stage, and further research is required at the seedling vegetative and reproductive stages for validation.Bangladesh J. Agri. 2024, 49(1): 117-127